The activity and isoforms of NADP-malic enzyme in Nicotiana benthamiana plants under biotic stress - Doubnerová, V; Jirásková, A; Janosková, M; Müller, K; Bat'ková, P; Synková, H; Cerovská, N; Ryslavá, H (General physiology and biophysics, 2007)
The activity and presence of isoforms of NADP-dependent malic enzyme (NADP-ME, EC 1.1.1.40) were studied in non-transgenic and transgenic Nicotiana benthamiana plants containing potyviral gene for helper component protease (HC-pro) and in plants infected by Potato virus Y strain NTN (PVY(NTN)). No significant changes in enzyme activities and isoenzyme pattern were observed due to foreign gene introduction and PVY(NTN) infection. However, the activity and isoenzyme composition of NADP-ME measured in extracts from different parts of the plants showed significant differences. Non-denaturating electrophoresis followed by specific detection of NADP-ME activity in polyacrylamide gel detected the presence of only one isoform in roots and younger leaves. Two isoforms of NADP-ME were detected in older leaves and stem (relative molecular mass approximately 248,000 and approximately 280,000) and three isoforms corresponding to tetramer, dimer and monomer were found in flowers. The activity of NADP-ME and the isoenzyme pattern was discussed in relation to its role in plant metabolism within distinct plant parts.
Keywords: Electrophoresis, Polyacrylamide Gel; geneticky modifikované rostliny; Nicotiana; transport proteinů; Isoenzymes; malátdehydrogenasa; Plants, Genetically Modified; elektroforéza v polyakrylamidovém gelu; izoenzymy; Potyvirus; Protein Transport; tabák; nemoci rostlin; Malate Dehydrogenase; Plant Diseases